2011
DOI: 10.5047/eps.2011.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of GPS TEC measurements with IRI TEC prediction at the equatorial latitude station, Chumphon, Thailand

Abstract: We have analyzed the total electron content (TEC) derived from dual-frequency GPS receivers (GPS TEC) at the Chumpon station, Thailand, during the period [2004][2005][2006]. The diurnal, monthly, and seasonal variation in the measured TEC is compared with the TEC derived from the IRI-2007 model as well as the TEC obtained from the International GNSS service (IGS). To date, TEC data at equatorial latitudes are limited. The Chumphon station (10.72• N, 99.37• E) is located at the equatorial latitude and the dip l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 34 publications
3
30
0
Order By: Relevance
“…The largest discrepancy (overestimation) in the IRI-2012 model TEC with the IRI-2001 topside has been observed during the daytime hour in equatorial and low-latitude regions (NTUS, CUSV, and KUNM). One possible cause for the daytime discrepancy in the IRI-2012 model may be the daytime ionospheric expansion, and as a result, a larger slab thickness is covered at around noon time as compared to other times (Kenpankho et al 2011). This expansion is larger at low latitudes as compared to mid latitudes.…”
Section: Discussionmentioning
confidence: 99%
“…The largest discrepancy (overestimation) in the IRI-2012 model TEC with the IRI-2001 topside has been observed during the daytime hour in equatorial and low-latitude regions (NTUS, CUSV, and KUNM). One possible cause for the daytime discrepancy in the IRI-2012 model may be the daytime ionospheric expansion, and as a result, a larger slab thickness is covered at around noon time as compared to other times (Kenpankho et al 2011). This expansion is larger at low latitudes as compared to mid latitudes.…”
Section: Discussionmentioning
confidence: 99%
“…All these effects are proportional to the Integrated Electron Content (IEC) which in turn intimately depends on Ne distribution along the ray-path, connecting satellite to receivers. However, IEC delivers one of the most important quantitative characteristic (Kenpankho et al, 2011) about the vertical framework of ambient ionosphere. DasGupta et al (2007) have reported that large spatial gradient in Total Electron Content (TEC; 1TECU = 10 16 el/m 2 ) variations exist in the equatorial ionosphere.…”
Section: Introductionmentioning
confidence: 99%
“…The IRI model permits, among other things, the reconstruction of the electron density profiles up to plasmaspheric heights and the TEC prediction. However, many studies compared the TEC derived from IRI and GNSS and show systematic bias in the IRI-TEC (e.g., Kenpankho et al 2011;Orús et al 2002). These discrepancies are interpreted by the lack of knowledge of the upper part of the ionosphere (e.g., Iwamoto et al 2002) and lead to a focus on the improvement of the topside ionospheric models in IRI (Bilitza et al 2006).…”
Section: Introductionmentioning
confidence: 99%